Download presentation

Presentation is loading. Please wait.

Published byBarrie Smith Modified over 8 years ago

2
4x + 2y = 18 a. (1,8)4 + 16 = 18 a. 4(1) + 2(8) = 18 b. (3,3)20 = 18 b. 4(3) + 2(3) = 18 12 + 6 = 18 18 = 18 15x + 5y = 5 a. (-2,7) NoYes b. (-1,4) a. 15(-2) + 5(7) = 5b. 15(-1) + 5(4) = 5 -30 + 35 = 5-15 + 20 = 5 5 = 5 Yes

3
y = 2x + 10 x y 1y = 2(1) + 1012 0y = 2(0) + 1010 y = 2(-1) + 108 (1,12) (0,10) (-1,8) y = -x + 5 x y 1y = -1(1) + 54 0y = -1(0) + 55 y = -1(-1) + 56 (1,4) (0,5) (-1,6)

4
4x + 2y = 20 -4x 2y = -4x +20 22 y = -2x +10 5x + y = -5 -5x y = -5x - 5

5
y = 4x - 1 x y y = 4(-1) - 1-5 0y = 4(0) - 1 1y = 4(1) - 13 y = -3x + 1 x y y = -3(-1) + 14 0y = -3(0) + 11 1y = -3(1) + 1-2

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google